Characterization of Eastern Mediterranean dust storms by area of origin; North Africa vs. Arabian Peninsula. (1st February 2019) - Bodenheimer, Shalev; Lensky, Itamar M.; Dayan, Uri
Abstract: The Eastern Mediterranean (EM) Basin is exposed to frequent dust storms during all seasons but summer. The dust is originating from two large sources: a western source, namely North African (mainly Sahara Desert) and an eastern source, the Arabian Peninsula. The characteristics of 53 dust storms (2007–2013) were examined in relation to their origin – western (30) vs. eastern (23). Analysis was done using ground monitoring stations, satellite data and subjective synoptic classification. Significantly higher ground concentration (722 μg/m 3 for western events vs 242 μg/m 3 for eastern events), higher Aerosol Optical Thickness (AOT) levels (0.50 for western events vs 0.32 for eastern events), longer duration (25 h for western events vs 15 h for eastern events) and stronger surface wind speed (6 m/s for western events vs 4 m/s for eastern events) were found for western origin dust storms. Dust top height was higher for eastern origin events (1.7 km for western events vs 2.3 km for eastern events, non significant). The associated synoptic circulation types dominant during the western origin dust storms are winter cold-core cyclones while for the eastern origin events the Red Sea Trough is the dominant type and occur mainly during fall. The main assumed reasons for these distinguished characteristics (higher ground concentration, AOT levels, longer duration, and surface wind speed) are that western origin cyclones can induce both mobilization and transport of dust. Together with longer dust path and local sources contribution will create a potential for high concentration and long-lasting event as compared to eastern origin events where there is a separation between main mobilization process that occur during summer and the transport westwards necessary to deliver dust to the EM and occurs during non-summer events. Highlights: We compared between western and eastern origin dust storms over the Eastern Mediterranean (EM). Western (North Africa) origin events have significantly higher PM10 concentrations, AOT levels and wind speed. Eastern (Arabian Peninsula) origin events have higher top height values, although not significant. The separation between the two sources is determined by the prevailing synoptic conditions over the EM through mobilization and transport processes.